Active games in physical education students of special medical group with limited capacity of cardiovascular system - M.V. Kovaleva (Physical Education of Students, 2013)
It is considered the directions of the development an effective methods of usage moving elements of sports and games in exercises. The experiment involved students of special medical groups that have various abnormalities of the cardiovascular system. The study was conducted in four stages: a search, the first experimental, the second experimental, final. We used questioning and education registry books of academic work. Found that the use of sports and outdoor games is students' interest, and increasing motivation for physical activity. Justified by the possibility of using games and exercises performed their adaptation by changing the pulse value. The resulting modification of gaming exercises are divided into three groups: the game in the area of heart rate to 110, 110-130 and 130-150 beats per minute. The first version of the experimental procedure at a heart rate of 110 and 110-130 beats per minute was ineffective for the emergence of significant positive changes in the functional state of the cardiovascular system students. Recommended experimental procedure based on the alternation and equivalence ratio of mobile elements and sports games and increases the heart rate to 130-150 beats per minute. Application of the method increases the overall level of physical health, improves the functional state of the cardiovascular system, health, activity and mood of the students.